The Limits of the Vernacular: Censorship of Vulgarisms in the Publishing Process of Kristijonas Donelaitis’ Works - Šeina, Viktorija (Tautosakos darbai, 2025)
The article analyzes expurgation and euphemization of rough vernacular lexis and phraseologisms in the process of publishing Kristijonas Donelaitis’ works in the 19th–20th centuries. Most frequently, words indicating the processes of physiological excretion, and phraseologisms formed using them were cut out or changed. All cases of euphemization of K. Donelaitis’ vulgarisms are discussed in the article, explaining how they changed the style, semantics and meter of the poetic work.Using Pierre Bourdieu’s theoretical approach to the sociology of language, the article examines the linguistic attitudes of the editors of K. Donelaitis’ works in the sociocultural context of the time. It is assumed that the editors’ decision to remove vulgarisms from K. Donelaitis’ works could also have been influenced by their desire to ensure the poet a central position in the canon of national literature. Although this article focuses on censorship of K. Donelaitis’ vulgarisms, it reflects the general dynamics of restrictions imposed on vernacular lexis that took place in the Lithuanian culture in the 19th–20th centuries.
Keywords: Kristijonas Donelaitis; vulgarism; censorship; linguistic habitus; canon